Egy nyugat-magyarországi elektronikai alkatrészeket gyártó nagyvállalat pénzgazdálkodásának és pénzügyi helyzetének elemzése - Tóth Dóra (2016)
I spent my traineeship at a West-Hungarian multinational company specialised in producing electronic components. The company itself has been dealing with the manufac-ture of aluminium electrolytic capacitors, inductors, choking-coils and voltage protection devices. Previously the company was divided into two locations, however, recently the plant from Szent László street has moved to Csaba street. By merging the two manifactur-ing sites the company has created a new, complex industrial area. The pursuit of my thesis is to analyse the budgetary management and the financial situation of this company. To be able to complete this task I used officially submitted bal-ance sheets, profit and loss statement and the appendixes of the last three fiscal years. These data are public, available for anyone and can be read on an electronic portal. While analysing the documents my primary target was to have a look into the operation of a mul-tinational company and gain a comprehensive view on the financial position of the enter-prise. Having finished the analyses and examining the results I could conclude that since the distribution of the dividends in 2013 the financial situation of the company is stable. The main changes, which could be observed in the increase of the values of the fixed as-sets and current liabilities, took place in 2015. That period is also significant because of the construction of the new plant and main office building. Furthermore in February 2015 the sales organization was altered as well: since then there is no direct connection between the company and its European customers anymore. The sales organization has been cen-tralized, all sales activities towards the EU customers have been taken over by the head-quarter. All things considered, both the construction and both the change of the sales channel have influenced the financial position of the company.